Quantifying the trade in wild-collected ornamental orchids in South China: Diversity, volume and value gradients underscore the primacy of supply. (October 2019) - Gale, Stephan W.; Kumar, Pankaj; Hinsley, Amy; Cheuk, Mang Lung; Gao, Jiangyun; Liu, Hong; Liu, Zhi-Long; Williams, Sophie J.
Abstract: Despite the grave threat illegal wildlife trade poses to species survival, few studies have attempted to link supply and demand data for the same wildlife product. All ca. 29, 000 orchid species are listed by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and many are protected under domestic legislation too, but a growing body of evidence suggests that orchids continue to be subject to unsustainable harvesting and undocumented trade. South China is a known black spot for trade in wild-collected ornamental orchids but understanding of the drivers determining the flow of species diversity, volume and value remains wanting. We conducted systematic monthly surveys at five markets along a West-East transect from Yunnan to Hong Kong for one year, recording variables including species, numbers of individuals, weight and price. Although wild orchid diversity is highest in Yunnan, the diversity of orchids in trade increased eastwards and mean price per stem rose more than four-fold, albeit always significantly cheaper than that for artificially produced hybrids. Part of this trade appears to be in breach of CITES. Few orchids in trade conformed to six criteria highlighted in prior demand-side studies as being of higher utility value, but most conformed to a combination of four or more, suggesting that vendors can readily offer products that meet a majority of consumer preferences. Effective supply-side regulation, through government intervention and social media campaigns, is needed to facilitate behavioural change and allow artificially propagated plants to compete in the market-place. Highlights: Wild orchid trade in South China involves >1.2 million individuals annually. At least part of this trade is in breach of CITES. Diversity and value are concentrated at markets far from the orchids' source. Wild-collected orchids are priced significantly cheaper than nursery-grown ones. Most wild orchids in trade conform to a majority of stated consumer preferences.